Addiction to Online Video Games among First Year Medical Students of a College located in Western India - Darshana Zala; Shobha Misra (Indian Association of Preventive and Social Medicine, 2022)
Introduction: The elderly population is growing much faster. Ageing is a global phenomenon and it is expected that by 2050 every country in the world will have substantial increase in population aged 60 years and above. Malnutrition is common among older people over 60 years of age. They are likely to experience morbidity, premature mortality, poor quality of life and reduced functional ability than normally nourished persons. Malnutrition increases health care costs, reduces productivity, and slows economic growth, which can perpetuate a cycle of poverty and ill-health. Hence combating malnutrition in all its forms is one of the greatest global health challenges. Objective: 1) To assess the nutritional status among elderly population in Hyderabad. 2) To assess the risk factors which are associated with malnutrition among elderly population. Method: A Cross sectional study was conducted in July - September 2021 among elderly persons aged 60 years and above residing in urban slums of Hyderabad. Considering the estimated prevalence of malnutrition among elderly population to be 14.5%, the sample size was calculated as 198 and was rounded off to 200. Data was entered into Microsoft Excel and analysed using Epi Info version 7.2.2.6. A predesigned, pre-tested questionnaire was used to collect data. Malnutrition was assessed using Mini Nutritional Assessment (MNA). Results: Among 200 participants, 52.5% were females. The mean age of the study population was 68.3 years. Among them 18% of the study participants were malnourished, 27% were at risk of malnutrition and 55% had normal nutritional status. Conclusion: Early diagnosis and prompt treatment of elderly people at high risk for malnutrition may improve their nutritional status and prognosis.